Facile synthesis of earth-abundant and non-toxic p-type Si96B4/SiCp nanocomposites with enhanced thermoelectric performance. (1st March 2018) - Upadhyay, Naval Kishor; Kumaraswamidhas, L.A.; Gahtori, Bhasker; Muthaiah, Saravanan; Bathula, Sivaiah; Shyam, Radhey; Dhar, Ajay
Abstract: One of the impediments in the development of thermoelectric devices for power generation is that they mostly contain toxic and expensive elements and/or are synthesized using expensive or time-consuming material processing methodology. We report the synthesis of Silicon–Boron (Si96 B4 ) alloy employing earth abundant constituent element using a facile single-step reactive sintering using spark plasma sintering technique. In order to enhance its mechanical properties, the synthesized Si96 B4 alloy was dispersed with SiC nanoparticles and the effect of its addition on the thermoelectric and mechanical properties in the resulting Si96 B4 /SiC nanocomposite has been investigated. A thermoelectric figure-of-merit ZT ~ 0.27 at 1123 K was realized at an optimized composition of Si96 B4 /1 wt% SiC nanocomposite. This enhancement in ZT primarily originates from a noticeable reduction in the thermal conductivity on SiC dispersion in Si96 B4 alloy, owing to the scattering of heat-carrying phonons by nanoscale SiC particles and mesoscale SiB3 precipitates, formed in-situ. The synthesized samples were characterized using X-ray diffraction and field emission scanning electron microscopy, based on which the enhancement in their thermoelectric and mechanical properties are discussed. Considering the low-cost and non-toxicity of the constituent elements coupled with facile and up-scalable one-step processing employed in its synthesis, Si96 B4 /SiC nanocomposites could be a potential p-type thermoelectric material for high-temperature power generation applications.